2004
DOI: 10.1021/je034261a
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties of Imidazolium-Based Ionic Liquids

Abstract: Ionic liquids (ILs) are salts that are liquid at low temperatures, usually including the region around room temperature. They are under intense investigation, especially as replacement solvents for reactions and separations, since they exhibit negligible vapor pressure and would not, therefore, contribute to air pollution. Clearly, basic thermophysical properties are vital for design and evaluation for these applications. We present density as a function of temperature, melting temperatures, glass-transition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

162
1,194
16
15

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,430 publications
(1,387 citation statements)
references
References 31 publications
162
1,194
16
15
Order By: Relevance
“…Very recently, Liu et al investigated the 1-butyl-3-benzylimidazolium bromide ([C 4 BnIM + ][Br − ]) IL for the extraction of Pt(IV) and Pd(II) using a LLE technique [11]. In this study, the IL was dissolved in chloroform to lower the viscosity of the extraction phase and subsequently mixed with an aqueous solution containing metal ions.…”
Section: Ils As Solvents For Lle and Matrix Dissolutionmentioning
confidence: 99%
See 4 more Smart Citations
“…Very recently, Liu et al investigated the 1-butyl-3-benzylimidazolium bromide ([C 4 BnIM + ][Br − ]) IL for the extraction of Pt(IV) and Pd(II) using a LLE technique [11]. In this study, the IL was dissolved in chloroform to lower the viscosity of the extraction phase and subsequently mixed with an aqueous solution containing metal ions.…”
Section: Ils As Solvents For Lle and Matrix Dissolutionmentioning
confidence: 99%
“…The authors discovered that an insoluble complex was formed when the bromide ions of the IL exchanged with [PtCl 6 -2 ]. For Pd(II), IR spectroscopy and single crystal X-ray diffraction studies revealed a strong dependence on the cation of the [C 4 BnIM + ][Br − ] IL for the extraction of the IL-Pd(II) complex from aqueous solution.…”
Section: Ils As Solvents For Lle and Matrix Dissolutionmentioning
confidence: 99%
See 3 more Smart Citations